PENGARUH UKURAN PERUSAHAAN, VARIABILITAS PERSEDIAAN, VARIABILITAS HARGA PKOK PENJUALAN, LABA SEBELUM PAJAK, DAN FINANCIAL LEVERAGE TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN (Pada Perusahaan Manufaktur Yang Terdaftar di BEI 2014-2018) - Mulia Andirfa; maryana; eka chyntia (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2022)
This study aims to determine "The Influence of Company Size, Inventory Variability, Variability of Cost of Goods Sold, Profit Before Tax, Financial Leverage on Inventory Selection Inventory Accounting Method (In Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange Period 2014-2018)" . . The population of this study are food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018. The research sample consisted of 7 companies. The sampling technique was purposive sampling technique. The data used are secondary data from the annual reports of food and beverage companies listed on the Indonesia Stock Exchange. This research uses logistic regression analysis method with SPSS program. The result of this research shows that firm size, inventory variability, cost of goods sold profit before tax simultaneously affect the selection of inventory accounting methods.